Diverting Stoma for Refractory Ano-perineal Crohn's Disease: Is It Really Useful in the Anti-TNF Era? A Multivariate Analysis in 74 Consecutive Patients. (19th November 2018) - Hain, Elisabeth; Maggiori, Léon; Orville, Marion; Tréton, Xavier; Bouhnik, Yoram; Panis, Yves
Abstract: Background and Aims: Faecal diversion [FD] can be proposed in patients with refractory anoperineal Crohn's disease [APCD]. This study aimed to assess long-term results of this strategy, following the advent of the anti-tumour necrosis factor [TNF] era. Methods: All patients who underwent FD for refractory APCD between 2005 and 2017 were included, excluding patients with a history of ileal pouch-anal anastomosis. A multivariate analysis regarding absence of stoma reversal [SR] was performed. Results: A total of 65 consecutive patients who underwent FD for APCD (comprising anoperineal fistula [ n = 40, 62%], rectovaginal fistula [ n = 21, 32%], fissures and/or ulceration [ n = 9, 14%], and/or anal stricture [ n = 5, 8%]) were included. At the time of FD, 34 patients [52%] presented with small bowel Crohn's disease [CD] involvement, 29 [45%] with colonic involvement, and 19 [29%] with rectal involvement. Following FD, 54 patients [83%] were treated with anti-TNF therapy, prescribed for isolated APCD [ n = 10, 15%] or luminal CD with APCD [n = 44, 68%]. After a mean follow-up of 49 ± 29 [7–120] months, SR was not possible in 32 patients [49%], including 17 patients [26%] requiring a subsequent proctectomy with abdominoperineal excision. In multivariate analysis, rectal CD involvement was the only independent factor associated with a reduced rate of SR (odds ratio: 4.0 [1.153–14.000]; p = 0.029), and anti-TNF therapy had no impact on SR rate. Conclusions: FD can be performed in selected patients with refractory APCD, to avoid abdominoperineal resection. However, this strategy should be proposed with caution in patients presenting with rectal CD involvement. Anti-TNF therapy has no impact on SR rate.